Use of Microsoft Teams and Youtube in the Application of E-Learning to Improve Student Learning Outcomes in Three-Dimensional Material - Wahyu Sugiarto (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The objectives of this study were (1) to increase the motivation to learn the mathematics of students of XII MIPA-2 with three-dimensional material through the application of E-learning using Microsoft Teams and Youtube, (2) to increase the mathematics learning achievement of students of XII MIPA-2 with three-dimensional material through the application of E-learning using Microsoft Teams and YouTube. The method used is classroom action research. Data collection through tests and non-tests. The test technique is to determine learning achievement using the items while the non-test technique is to determine the development of learning motivation using observation sheets. Data analysis used comparative descriptive for learning achievement data and qualitative descriptive for learning motivation data. The results of this classroom action research showed that the students 'motivation to learn mathematics increased from low to high and the average score of students' mathematics learning achievement increased by 20.85% from 65.05 to 78.61 with an increase in completeness level of 57.88%, namely from 52, 78% to 83.33%, so theoretically and empirically through the application of E-learning using the Microsoft Teams and Youtube application it can improve the results of motivation and achievement in learning mathematics in three-dimensional material for students of class XII MIPA-2 SMA Negeri 1 Jepara in the odd semester of 2020 -2021. Keywords: E-learning, Microsoft Teams, Youtube, three dimensions.